To complete the expression and solve for the radical equation in the form:
\[ \sqrt{a} - \sqrt{b} = \sqrt{c} \]
Let's assign integers to \(a\), \(b\), and \(c\). Not all values need to be the same, and the radicals should be composed of integers where necessary.
Let's take a specific example:
- Let's say \( \sqrt{8} - \sqrt{2} = ?\)
- We know: \[ \sqrt{8} = 2\sqrt{2} \] Therefore: \[ 2\sqrt{2} - \sqrt{2} = (2 - 1)\sqrt{2} = 1\sqrt{2} \]
From the above, we can substitute \(c\): \[ c = 2 \]
Thus, we have:
\[ \sqrt{8} - \sqrt{2} = \sqrt{2} \]
In our example, the values are:
- \( a = 8 \)
- \( b = 2 \)
- \( c = 2 \)
You can choose different values for \(a\), \(b\), but you would still arrive at the conclusion that when subtracting radicals, they need to be similar to simplify directly.